Which yield curve spread is the best for predicting the recessions in the U.S economy? A wavelet approach - Özmen, Mehmet İkbal (İstanbul Bilgi Üniversitesi, 2019)
Using out-of sample methods, we compare the performance of the wavelet-based probit model and standard probit model in forecasting recession in the U.S. Additionally, the performance of different financial indices, such as term spreads, credit spreads, interest rates, was evaluated in both the wavelet-based probit model and the standard probit model. The out-of-sample exercises are employed respectively for three, six, twelve and twenty-four-months ahead forecasts. We use four different wavelet filtering methods including Haar, Symlet, Coiflet and Daubechies to obtain low frequency fluctuations of observed series. According to numerical results, forecasting performance of the wavelet-based model outperforms standard probit model for three, six and twelve month-ahead forecasting. Moreover, the yield curve spread between between 3-Y ear Treasıny Constant Maturity Rate - 1-Y ear Treasury Constant Maturity Rate and the yield curve spread between between 3-Year Treasury Constant Maturity Rate - Federal Funds Rate among indexes have better results in forecasting a recession in the U.S.

Örnek dışı yöntemleri kullanarak, dalgacık tabanlı probit modelinin ve standart probit modelinin ABD'deki ekonomik durgunluk tahminindeki performansını karşılaştırırız. Ayrıca, dalgacık tabanlı probit modelinde ve standart probit modelinde vadeli spreadler, kredi spreadleri, faiz oranları gibi farklı finansal endekslerin tahmin performansı ölçülmektedir. Örneklerin dışı çalışmalar sırasıyla üç, altı, on iki ve yirmi dört aylık tahminlerde uygulanmaktadır. Gözlenen serilerin düşük frekanslı dalgalanmalarını elde etmek için, haar, symlet, coiflet ve daubechies olmak üzere dört farklı dalgacık filtreleme yöntemi kullanırız. Sayısal sonuçlara göre, dalgacık tabanlı modelin tahmin performansı, üç, altı ve on iki ay öncesinden tahmin için standart probit modelinden daha iyi performans göstermektedir. Ayrıca, GS3MFFM ve GS3MGSl'in verim eğrisi dağılımları arasında ABD'de durgunluk tahmininde daha iyi sonuçlar olduğu görülmüştür.
ABD'de resesyonu tahmin etmek için hangi verim eğrisi yayılımı en iyisidir? Bir dalgacık yaklaşımı